Insulin resistance and metabolic diseases - a review - Marta Drabczyk; Kamila Kosyra; Inga Magda; Zuzanna Marczyńska; Antoni Zyśk (Kazimierz Wielki University, 2024)
Introduction: This review paper aims to discuss the effects of insulin resistance, and its association with various metabolic diseases. Insulin resistance (IR), characterized by diminished tissue responsiveness to physiological insulin levels, is a key component in various metabolic diseases, including type 2 diabetes, cardiovascular disorders (CVDs), obesity, and non-alcoholic fatty liver disease (NAFLD). State of knowledge The consequences of IR are profound; in type 2 diabetes, it hinders glucose utilization by muscle cells, leading to hyperglycemia, muscle damage, and loss of mass and strength. IR also plays a central role in NAFLD, promoting lipid accumulation, hepatic inflammation, fibrosis, and cell death. Materials and methods: A review of chosen literature in the PubMed  and Google Scholar databases was conducted, using the following key words: "Insulin resistane", "Insulin resistance in obesity", "Obesity", "Insulin resistance NAFLD", "Diebetes", "Insulin resistance CVD" Summary: The consequences of insulin resistance are far-reaching. In the context of type 2 diabetes, it impedes glucose utilization by muscle cells, resulting in hyperglycemia and subsequent muscle cell damage, contributing to loss of mass and strength. Insulin resistance is also a central player in the pathogenesis of non-alcoholic fatty liver disease (NAFLD), fostering lipid accumulation, hepatic inflammation, and, ultimately, fibrosis and cell death. Conclusions: In conclusion, understanding insulin resistance is paramount in addressing the rising prevalence of metabolic diseases globally Controlling insulin resistance emerges as a crucial aspect of managing these metabolic disorders and their complications. Further research into the mechanisms of IR formation and effective intervention strategies is imperative for improving public health outcomes.